THE ROLE OF LOCAL GOVERNMENT IN THE PROVISION OF BUDGET ASSOCIATED WITH THE DEVELOPMENT OF INTEGRATED WASTE FACILITY - I Gusti Ayu Eviani Yuliantari (Ganesha Law Review, 2019)
This research entitled “The Role of Local Government in The Provision of Budget Associated with The Development of Integrated Waste Treatment Facility”. This study used empirical research. Data of this study was collected through various techniques including interviews and requested data from the area under investigation. One of the permit requirements in the field of environmental law was that the activities of the business should have AMDAL ensures that the business activity would not cause major and significant impact on the environment. Environmental management and environmental law enforcement, should be implemented firmly and wisely. One of the policies implemented was to enter one of the documents in the environmental feasibility of the licensing of development are estimated to have an impact. Local government was not given to the indigenous village Ships fully, delays in awarding these funds, making the development of the Integrated Waste Management was still unrealized. As mandated in the law, and the money should be given as soon as the efforts to enforce the environmental oriented environmental sustainability itself.